The concept and challenges of medical professionalism - Marzieh Lashkari; Amin Beigzadeh (Islamic Azad University, 2014)
We argue that the field of medicine ought to think over the definition of medical professionalism and the challenges that doctors face in everyday practice. Although there are a diversity of definitions revolving around medical professionalism, but the most recent and revalidated definition should be taken into account. In addition, we highlight four barriers threatening professionalism: 1) doctors' of self-interest; 2) doctors' temptation to deviate from the standards of medicine; 3) market incentives (financial conflicts of interest); and 4) peer pressures. We conclude with suggestions for remedies to overcome these threats, e.g. selection criteria of medical students, and stringent rules and guidelines.